Using inerter-based isolator for passive vibration control of Michelangelo's Rondanini Pietà. Issue 1 (July 2017) - Siami, A.; Cigada, A.; Karimi, H.R.; Zappa, E.; Sabbioni, E.
Abstract: This paper proposes a passive vibration isolator methodology based on inerters for improving the performance of the famous statue of Michelangelo Buonarroti. More specifically, the five-degree-of-freedom (5DOF) model of the statue based on experimental tests has been presented. Using this developed model, the impact of actuation devices such as tuned mass-damper (TMD) and tuned mass-damper-inerter (TMDI) in vibration reduction of this structure is investigated. Then, the effect of TMDI on the 5DOF model accounting for physical limitations due to system parameters is presented. To have better insight into the effect of inerters in this case, some index functions have been used here. Finally, simulation results are provided to illustrate effectiveness of the passive element of TMDI in vibration reduction transmitted to the statue in vertical direction.